Efektivitas Computer-Assisted Language Learning Terhadap Penguasaan Kosakata Bahasa Arab: Studi Meta-Analisis - Irfan (Jurnal Ilmu Pendidikan Guru Sekolah Dasar dan Usia Dini, 2025)
This study aims to evaluate the effectiveness of using Computer-Assisted Language Learning (CALL) in improving Arabic vocabulary mastery through meta-analysis. A total of 10 experimental and quasi-experimental studies published in the last five years were analyzed to measure the impact of CALL on vocabulary mastery. The results of the meta-analysis showed a combined effect size value of 0.87, indicating a moderate to large effect of CALL on vocabulary learning. However, the heterogeneity of results across studies suggests that the effectiveness of CALL is influenced by factors such as the type of technology used, the level of learners' abilities, and the teaching context. These findings suggest that CALL can be an effective tool in improving Arabic vocabulary mastery, but proper implementation and pedagogical design tailored to students' needs are essential to achieve optimal results. This study also highlights the importance of further research to explore factors that moderate the effectiveness of CALL.